2012
DOI: 10.1063/1.4707734
|View full text |Cite
|
Sign up to set email alerts
|

A product branching ratio controlled by vibrational adiabaticity and variational effects: Kinetics of the H + trans-N2H2 reactions

Abstract: The abstraction and addition reactions of H with trans-N(2)H(2) are studied by high-level ab initio methods and density functional theory. Rate constants were calculated for these two reactions by multistructural variational transition state theory with multidimensional tunneling and including torsional anharmonicity by the multistructural torsion method. Rate constants of the abstraction reaction show large variational effects, that is, the variational transition state yields a smaller rate constant than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Troya and O’Neil reported theoretical reaction-dynamics properties for the N 2 H 4 + O reaction, such as the cross sections and product-energy distributions. On the basis of the experience gained in previous investigations of our group studying the hydrazine properties , and its reaction with hydrogen and nitrogen, the reaction with atomic oxygen has been studied by us in detail as well, reporting thermochemical properties and rate constants based on two reaction paths for the hydrogen abstraction by oxygen and achieving good agreement with the previous experimental results, ,, in particular lying within the estimated error determined by Shane and Brennen . In qualitative agreement with Gehring et al, , our calculated rate constants showed a positive dependence on the temperature.…”
Section: Introductionsupporting
confidence: 89%
“…Troya and O’Neil reported theoretical reaction-dynamics properties for the N 2 H 4 + O reaction, such as the cross sections and product-energy distributions. On the basis of the experience gained in previous investigations of our group studying the hydrazine properties , and its reaction with hydrogen and nitrogen, the reaction with atomic oxygen has been studied by us in detail as well, reporting thermochemical properties and rate constants based on two reaction paths for the hydrogen abstraction by oxygen and achieving good agreement with the previous experimental results, ,, in particular lying within the estimated error determined by Shane and Brennen . In qualitative agreement with Gehring et al, , our calculated rate constants showed a positive dependence on the temperature.…”
Section: Introductionsupporting
confidence: 89%
“…An additional noteworthy feature is that the observed major product 4c , resulting from the transformation of 3c , actually is separated from the precursor by a higher computed energy barrier than the minor product 3 A 2 - 2c . This contradicts the rules inferred from classical TST and cannot be explained in terms of a thermal over-the-barrier process, but only by considering the occurrence of heavy-atom QMT dominated by tunneling control . ,, …”
Section: Resultsmentioning
confidence: 69%
“…The model includes 38 species and 265 elementary reactions. It was constructed based on previous models; i.e., the H 2 subset was adopted from Hashemi et al, and the ammonia subset was mainly adopted from the Shrestha mechanism, replacing the rate constants of reactions NH 2 + H = NH + H 2 , N 2 H 2 + H = NNH + H 2 , and N 2 H 2 + M = NNH + H + M with more recent values. ,, The authors demonstrated the good performance of this mechanism for predicting the laminar burning velocity of ammonia mixtures under 0.1, 0.2, and 0.5 MPa. The mechanism also shows satisfactory performance for the ignition delay times measured in a shock tube (high temperatures and low to high pressures) by Mathieu and Petersen …”
Section: Combustionmentioning
confidence: 99%